Norma Perlindungan dan Kesempatan Kerja Bagi Lansia Potensial Ditinjau dari Asas Kepastian Hukum, Keadilan, dan Kemanfaatan - Murti Pramuwardhani Dewi (Kosmik Hukum, 2023)
This study aims to analyze the norms of protection and private employment opportunities for the Potential Elderly (elderly) in terms of the principles of legal certainty, justice, and benefit. The research on the norms of protection and employment opportunities for the elderly in terms of the principles of legal certainty, justice, and benefit is normative. Normative research was conducted by examining library materials (secondary data). The secondary data consists of primary and secondary legal materials using document studies. The results of this study were then analyzed qualitatively and presented in the form of a descriptive-analytical journal manuscript. Based on the results, can be concluded that the regulations of the norms of protection and employment opportunities for the Potential Elderly in private companies have not provided legal certainty and benefit, but have provided justice for the elderly to obtain job opportunities and services to improve their welfare.Keywords : Protection, employment opportunities, potential elderly